Motivations for volunteering: theoretical considerations and a proposal for operationalization - Klos, María Carolina; Lemos, Viviana Noemi (Pensando Psicología, 2019)
Introduction: Volunteering can be defined as non-spontaneous, planned long-term prosocial behavior provided in an organizational context and that actively seeks to benefit strangers (Penner, 2002). Objective: Given the interest in knowing the factors that drive a person to get involved and remain in voluntary service, the main theoretical considerations related to the motivations for volunteering are presented, proposing an instrument for its operationalization. Method: With the aid of five expert judges, an instrument consisting of 62 questions was built with the answer sheet adopting a 7-point Likert format. 320 young adults, aged 18 to 30 years (M = 22.34; SD = 3.36) participated in the study. Results: The psychometric properties of the scale were analyzed based on: a) the discriminative power of the items, b) the underlying structure of the test, and c) the internal consistency of the scale. The results obtained show adequate psychometric validity. Conclusions: The questionnaire for the evaluation of motivational reasons for volunteering could be a useful tool for recruiting volunteers, placing candidates in appropriate positions and designing strategies that encourage them to continue volunteering.